Treatment and prognosis of elderly patients with non-ST-elevation myocardial infarction. (3rd October 2022) - Van Den Broek, W W; Gimbel, M E; Hermanides, R S; Runnet, C; Storey, R F; Austin, D; Oemrawsingh, R M; Cooke, J; Galasko, G; Walhout, R; Schellings, D A A M; The, S H K; et al.
Abstract: Background/Introduction: Elderly constitute a large though specific group of patients presenting with non-ST elevation myocardial infarction (NSTEMI), as they are at higher risk of adverse cardiovascular events, as well as treatment-related complications. However as they underrepresented in clinical trials, the optimal management strategy for older patients with NSTEMI remains unclear. Purpose: The aim of this registry was to capture the medical and invasive treatment of elderly NSTEMI patients, find predictors for major adverse cardiovascular events (MACE) and estimate the impact of invasive management and revascularisation. Methods: The POPular AGE registry is a prospective, observational multicentre study of patients ≥75 years of age presenting with NSTEMI at multiple sites in the Netherlands, United Kingdom and Austria. Management was at the discretion of the treating physician. MACE consisted of cardiovascular death, acute coronary syndrome (ACS) and stroke. Net adverse clinical events (NACE) was defined as composite of all-cause death, ACS, definite stent thrombosis, stroke, or major bleeding (Bleeding Academic Research Consortium [BARC] bleeding 3 or 5). The population was stratified into an invasively treated group defined as patients who underwent coronary angiography (CAG); and a conservatively-treated group with patients who received medical treatment only. The duration of follow-up was one year. Clinical variables were assessed for their predictive value for MACE and bleeding by means of a Cox proportional hazard regression. Results: The total study population consisted of 1190 elderly patients with NSTEMI (median age 80 years [IQR 77–84], 43% female). Invasive treatment with CAG was performed in 67% of the population, of which 49% underwent PCI and 14% coronary artery bypass grafting (CABG). At discharge, the majority of patients (55%) were treated with dual antiplatelet therapy (DAPT). MACE occurred in 15% and major bleeding occurred in 5% of the total population. Age (HR 1.06, 95% CI 1.03–1.09), diabetes mellitus (HR 1.62, 95% CI 1.16–2.24), reduced LVEF (<50%) (HR 1.51, 95% CI 1.03–2.20), Killip class (HR 1.58, 95% CI 1.07–2.33) and electrocardiogram (ECG) changes at admission (HR 1.67, 95% CI 1.20–2.31) were predictors for MACE. MACE occurred more frequently in conservatively-treated than invasively-treated patients (20% vs. 12%, HR 0.52, 95% CI 0.38–0.70, p<0.001). Revascularization with PCI or CABG was associated with lower risk of MACE (PCI; HR 0.47, 95% CI 0.30–0.75, p=0.001 and CABG; HR 0.31, 95% CI 0.13– 0.73, p=0.008). Conclusions: In this prospective registry of NSTEMI patients of ≥75 years, MACE and major bleeding were frequent. Age, diabetes mellitus, reduced LVEF, Killip class and ECG changes at admission were independent predictors for MACE. Although subject to selection bias, undergoing CAG and revascularisation, when indicated, were associated with better outcomes. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca